Identification of mapping models of players cooperation in creating point situations in volleyball depending on setter position - Mazur, L.; Superlak, E. (Polish Journal of Sport and Tourism, 2018)
Introduction. Team games, which have been studied by researchers for several years, include both individual and cooperative actions. Although cooperation is the essence of team sports, there is still a dearth of research that has thoroughly explored the process of player cooperation. The aims of the current study are to identify the models of player cooperation in creating point situations depending on the position of the setter and evaluate the efficiency of this cooperation. The process of cooperation was analysed by means of praxeological models reproducing the game, considering the efficiency of the attack and the surprise effect on the opponent`s block. Material and methods. A novel research method was used in this study, which is the qualitative study of unique cases. The material analysed was the observation sheets from matches played by the four best teams of the top Polish volleyball league in the 2013/14 season. Results. The observations yielded a large amount of data, which enabled us to identify models of cooperation in creating point situations depending on the position of the setter during the game. We also evaluated the reliability of the attack and the effectiveness of surprising the opponent`s block. Conclusions. Each of the teams had a specific model mapping cooperation in creating point situations depending on the position of the setter on the court. Teams achieve different levels of attack reliability as well as of the surprise effect on the opponent`s block in these interactions.